Peran dan Tanggung Jawab Notaris/PPAT Terhadap Pembuatan Akta Jual Beli - Andi Ismayana Wahid; Firman Tongke (Prosiding SISFOTEK, 2023)
Notary and PPAT are the world of theory and practice. Where a notary has authority and responsibility that will continue to attach to him even if the notary has retired. In making authentic deeds, Notaries are ordinary people who sometimes make mistakes or mistakes which can cause losses to the parties, whether intentionally or unintentionally. If something like this happens, is the notary obliged to take responsibility? And to what extent are the roles and responsibilities of notaries as public officials in making authentic deeds in accordance with Law Number 30 of 2004 concerning the Position of Notaries in conjunction with Law Number 2 of 2014 concerning the Position of Notaries? The type of research that the author uses in preparing this legal writing is library legal research, this type of research is also called normative legal research. If the notary makes mistakes and makes negligence in making an authentic deed, then the notary can be held responsible for all the mistakes he made from a civil perspective, namely paying compensation, then responsibility from an administrative perspective, if proven to have made a mistake, he can be subject to sanctions in the form of a written warning, temporary dismissal, dishonorable dismissal, whereas from the perspective of criminal law, if it is proven that you intentionally and knowingly made and collaborated in the making and signing of a fake deed, you will be charged with the crime of being a part of deed falsification.